2010
DOI: 10.1016/j.juro.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Study of High Dose Ketoconazole Plus Weekly Docetaxel for Metastatic Castration Resistant Prostate Cancer

Abstract: Purpose High-dose ketoconazole and docetaxel have shown activity as single agents against castration-resistant prostate cancer (CRPC). The goal of this phase I study was to determine the maximum tolerated doses, side effects, and pharmacokinetic interaction of coadministered docetaxel and ketoconazole. Experimental Design Patients with metastatic CRPC received weekly docetaxel for 3 of every 4 weeks, plus daily ketoconazole. Pharmacokinetic studies were performed on day 1 (docetaxel alone) and day 16 (after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Some studies have reported clinical adverse effects after therapy with various systemic anti-fungal agents (Kim et al 2003;Figg et al 2010). Several case reports of mild-to-severe hepatic injury, including icteric and fatal cases, have been published (Kim et al 2003;Figg et al 2010). For instance, the adverse effects of griseofulvin include gastrointestinal symptoms, allergic reactions, photodermatitis, hepatic and renal dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported clinical adverse effects after therapy with various systemic anti-fungal agents (Kim et al 2003;Figg et al 2010). Several case reports of mild-to-severe hepatic injury, including icteric and fatal cases, have been published (Kim et al 2003;Figg et al 2010). For instance, the adverse effects of griseofulvin include gastrointestinal symptoms, allergic reactions, photodermatitis, hepatic and renal dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the adverse effects of griseofulvin include gastrointestinal symptoms, allergic reactions, photodermatitis, hepatic and renal dysfunctions. Similarly, the adverse effects of ketoconazole include hepatic dysfunction or asymptomatic increases in the activities of serum transaminases (Figg et al 2010). In addition, nausea and vomiting are observed in response to itraconazole treatment and flucanozole treatment can trigger severe gastro-intestinal complications (Gupta and Gregurek 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Median OS of chemotherapy-naive patients (n ¼ 27) in this study was 36.8 months. It is interesting to note, however, that patients who had previously progressing disease on docetaxel (n ¼ 15) had a median survival of 10.3 months when docetaxel was reintroduced with ketoconazole (67). Although this was a small trial, the OS of taxane-naive patients compares favorably with contemporary studies.…”
Section: Strategies For Overcoming Taxane Resistancementioning
confidence: 95%
“…may be feasible as well as the possible combination with chemotherapy. 27,28 MDV3100. MDV3100 is an orally bioavailable, organic, nonsteroidal small molecule targeting the androgen receptor with potential antineoplastic activity.…”
Section: Hormonal Strategiesmentioning
confidence: 99%